The Gorontalo City Government Performance in Borrowing and Financial Management - Arman Arman; Ishak Yussof (Universitas Medan Area, 2026)
Government performance is influenced by regional borrowing and the effectiveness of local financial management. This study aims to analyze the relationship between regional borrowing policies, financial management effectiveness, and local government performance. The research employs a case-study design with a mixed-methods approach, systematically integrating quantitative and qualitative methods to produce a comprehensive, context-sensitive analysis. The main finding of this study reveals that the Gorontalo City Government utilizes regional borrowing as an alternative financing source to bridge fiscal gaps, particularly for infrastructure development and the improvement of public service delivery. However, the impact of borrowing is not direct. The regression results indicate a very weak and statistically insignificant relationship between regional borrowing and government performance, as reflected by R = 0.017, R² = 0.000, and Sig. = 0.867. These findings imply that regional borrowing should be directed toward productive, high-leverage sectors rather than merely used to cover budget deficits. The study contributes to the development of government studies by demonstrating that local government performance is determined not only by the magnitude of fiscal resources but, more importantly, by the quality of governance. Its primary contribution lies in strengthening the understanding of the relationship between government legitimacy, public trust, political accountability, and executive–legislative relations.